Фортепьянные концерты Моцарта - Друскин Михаил Семенович (Библиотека слушателя концертов, 1959)
Экземпляры: ИСК (20121129) / Инвентарный номер: 0107044 / Цена: 0.90 / Сис.шифр: 85.313(3/8)-8 / Авт.знак: Д 76 / ГРНТИ: 18 / ББК: 85.313(4)-8